Synthesis and Characterization of New Xanthene Derivatives, and Their Electrochemical Study. Issue 2 (14th December 2015) - Saeed, Aamer; Shabir, Ghulam; Shehzadi, Syeda Aaliya
Abstract: This work investigated the synthesis of biphenyl‐3, 3′, 4, 4′‐tetracarboxylic dianhydride and benzophenone‐3, 3′, 4, 4′‐tetracarboxylic dianhydride derivatives (3a –e and6a –e ) with different substituted phenols via Friedel‐Crafts acylation reaction in the presence of dilute sulfuric acid. Dianhydride derivatives with 3‐N, N′‐dimethylamino phenol (3d and6d ) and resorcinol (3e and6e ) have been found to be highly fluorescent. The structures of all newly synthesized compounds were confirmed by the chromatographic, spectral and elemental data. Electrochemical study was done to determine to band gap energy, LUMO and HOMO levels energy. Band gap and LUMO energy levels were found to be lowest in xanthene derivatives substituted with 3‐N, N′‐dimethylamino group having value 2.24 and 4.85 eV respectively. Abstract : The present investigation deals with the synthesis of double dianhydride based symmetric xanthene dyes. Condensation occurred through Friedel Crafts acylation reaction. The derivatives comprising resorcinol and 3‐N, N‐dimethylaminophenol condensed with dianhydrides proved to be highly fluorescent. The emission occurred at longer wavelength as compared to well known fluorescent xanthene dyes, Fluorescein and Rhodamine 6G. The target compounds exhibited redox potential during electro chemical study.